Placenta previa may acquire invasive nature by factors associated with epithelial‐mesenchymal transition and matrix metalloproteinases. Issue 12 (13th September 2020) - Soyama, Hiroaki; Miyamoto, Morikazu; Ishibashi, Hiroki; Iwahashi, Hideki; Matsuura, Hiroko; Kakimoto, Soichiro; Suzuki, Rie; Sakamoto, Takahiro; Hada, Taira; Takano, Masashi
Abstract: Aim: To investigate the differences in epithelial‐mesenchymal transition (EMT)‐ and matrix metalloproteinases (MMP)‐related factors among placenta previa with and without placenta accreta spectrum (PAS) ( n = 69), and normal placenta ( n = 51). Methods: The women diagnosed with placenta previa with or without PAS, and normal placentas, who delivered at our institution between 2006 and 2016, were enrolled. The difference of EMT‐related factors' expression by immunochemical analysis in chorionic villi and decidual cells between the normal placenta and placenta previa with or without PAS were evaluated. Results: In chorionic villi of placenta previa with and without PAS, E‐cadherin expression decreased, while that of ZEB1, SNAIL2 and MMP‐9 increased than that in normal placenta. In decidual cells of placenta previa with and without PAS, expression of vimentin, ZEB1 and MMP‐9 increased than that in normal placenta. In placenta previa with and without PAS, there was strong co‐expression of ZEB1 and vimentin in chorionic villi, of ZEB1 and MMP‐2 or MMP‐9 in decidual cells, and of SNAIL2 and vimentin or MMP‐9 in both chorionic villi and decidual cell. Vimentin expression in both chorionic villi and decidual cells was higher in placenta previa with PAS ( n = 18) than in placenta previa without PAS ( n = 51). MMP‐2 expression in decidual cells was higher in placenta previa with PAS than in placenta previa without PAS. Conclusion: This study revealed that EMT‐ and MMP‐associated factors may be related to placenta previa with and without PAS. Furthermore, placenta previa without PAS may acquire invasive nature.